Synthesis of Cellulose Straw and Rice Husk as Raw Materials for Bioplastic Production - Hardi, Gilar Wisnu; Dewi, Berlian Kusuma; Toruan, Sari Artauli Lumban; Nurjanah, Suci; Fitriana, Syifa Ayu; Yunita, Lia (Universitas Pendidikan Mandalika, 2024)
The development of environmentally friendly materials such as bioplastics is a solution to reduce the negative impact of conventional plastics on the environment. This study presents a novel approach by utilizing hemicellulose extracted from rice straw and husks—abundant agricultural waste materials—as the main raw materials for bioplastic production. Hemicellulose was extracted using the alkalization method, and its characterization was carried out through FTIR analysis to identify typical polysaccharide functional groups. The results of the analysis showed the presence of O-H, C-H, and C-O-C groups, which indicate the glycosidic structure of hemicellulose, as well as indications of residual lignin with C=C groups. The resulting hemicellulose was then processed into bioplastics with the addition of plasticizers and reinforcing materials, incorporating glycerin, CMC, and TiO₂ to enhance mechanical properties and biodegradability. Mechanical and degradation tests demonstrated superior performance, highlighting the synergy between these additives. This study provides an innovative strategy for transforming agricultural waste into high-value bioplastics, contributing to sustainability and advancing green material technology.